The stability of polyaromatic naphthalene sulfonates in hydrothermal solutions to 330 °C at equilibrium saturated vapour pressure. (September 2022) - Sajkowski, Lucjan; Seward, Terry M.; Mountain, Bruce W.; Marynowski, Leszek
Highlights: The thermal breakdown rate of 2, 6-naphthalene disulfonate (2, 6-NDS); 2, 7-naphthalene disulfonate (2, 7-NDS); 1, 5 naphthalene disulfonate (1, 5-NDS); and 1, 6-naphtahlene disulfonate (1, 6-NDS) has been measured at different conditions. 1-naphthol, 2-naphthol, 1-chloronaphthalene and naphthalene have been detected as breakdown products of 1, 6-NDS at ≥ 200 °C. The breakdown products of 1, 6-NDS can be potentially useful as geothermal tracers. The assumption of NDS long term stability during a tracer test needs to be done with caution. Abstract: Naphthalene sulfonates and disulfonates have been widely used in the geothermal industry as tracer chemicals and knowledge of their rates of thermal breakdown is essential to ensure their successful use. In this study the stabilities of six polyaromatic sulfonates: 1-naphthalene sulfonate (1-NS); 2-naphthalene sulfonate (2-NS); 2, 6-naphthalene disulfonate (2, 6-NDS); 2, 7-naphthalene disulfonate (2, 7-NDS); 1, 5- naphthalene disulfonate (1, 5-NDS); and 1, 6-naphtahlene disulfonate (1, 6-NDS) in 0.050 mol kg −1 NaCl solution was investigated. The NDS/NS thermal stabilities were studied as a function of temperature and pH in oxygen-free solutions. Three sets of experiments were conducted using quartz glass ampoules. The first set of experiments studied the breakdown rates of both 1, 5-NDS and 2-NS at a range of pH values at 200 and 300 °C. The second set studied 1, 6-NDS thermal decay to determine the breakdown products at 200, 250, and 300 °C. The third set involved a mixture of 1, 5-NDS, 1, 6-NDS, 2, 6-NDS, 2, 7-NDS, and 2-NS in 0.050 mol kg −1 NaCl, with and without the presence of greywacke, at temperatures up to 300 °C. The results show that 1, 5-NDS and 2-NS breakdown is temperature and pH-dependent. The breakdown of 1, 6-NDS forms mainly 2-naphthalene sulfonate (2-NS), whereas above 300 °C, 1, 6-NDS generated significant amounts of naphthalene (NAP). The results show that the stabilities of all tested NDS/NS compounds are temperature-dependent with their relative stabilities increasing in the order 1, 5-NDS < 1, 6-NDS < 2, 6-NDS ≈ 2, 7-NDS < 2-NS. In the presence of greywacke, fluid-rock interactions served to buffer pH thereby stabilizing the NDS over experiments where no rock was present. The finding presented in this study support need for reevaluation of historic NDS tracer tests, and consideration of reservoir temperature and pH when planning future tests.